América Latina y Estados Unidos Historia y política país por país - COCKCROFT, James D. (SIGLO VEINTIUNO, 2001)
Otros descriptores: HONDURAS; NICARAGUA; COSTA RICA; PANAMA; EL CARIBE; PUERTO RICO; REPUBLICA DOMINICANA; VENEZUELA; COLOMBIA; ECUADOR; PERU; BOLIVIA; PARAGUAY; CHILE; HISTORIA ARGENTINA; URUGUAY; BRASIL